2008
DOI: 10.1002/elps.200700494
|View full text |Cite
|
Sign up to set email alerts
|

Cationic surfactants for micellar electrokinetic chromatography: 1. Characterization of selectivity using the linear solvation energy relationships model

Abstract: MEKC and the linear solvation energy relationship (LSER) model have been applied to two series of cationic surfactants. The synthetic flexibility of the quaternary ammonium group is exploited to generate the two series, one consisting of linear substitutions and the other incorporating the ammonium into ring structures of varying size. The effects of the head group structure on the CMC, aggregation number, and electrophoretic properties of the surfactants were determined. These surfactants were also characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 45 publications
0
27
1
Order By: Relevance
“…Our group has recently reported the synthesis of two series of cationic surfactants with systematically varied headgroup structure and the characterization of their retention and selectivity in EKC using the linear solva-tion energy relationship (LSER) model [10]. Our results showed that slight structural changes to the headgroups of cationic surfactants produce significant changes in retention and selectivity.…”
Section: Introductionmentioning
confidence: 62%
“…Our group has recently reported the synthesis of two series of cationic surfactants with systematically varied headgroup structure and the characterization of their retention and selectivity in EKC using the linear solva-tion energy relationship (LSER) model [10]. Our results showed that slight structural changes to the headgroups of cationic surfactants produce significant changes in retention and selectivity.…”
Section: Introductionmentioning
confidence: 62%
“…Study of Schnee and Palmer [9] Logk CTAB ¼ NA þ 0:65ð0:13ÞE À 0:58ð0:11ÞS þ 1:06ð0:09ÞA À 2:77ð0:18ÞB þ 3:28ð0:22ÞV ð12Þ …”
Section: Resultsmentioning
confidence: 99%
“…Schnee and Palmer [9] did not report a numerical value for the constant, nor did the authors give the complete statistical details for their derived correlation. Examination of Equations 11 -13 reveals that the Abraham model does provide a very good mathematical description of each of the three log k CTAB datasets.…”
Section: Full Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…The identity and LSER descriptors of 40 compounds are presented in [13]. The current study used the same compounds, minus bromobenzene, for a total of 39 analytes.…”
Section: Methodsmentioning
confidence: 99%